Answer to Question #136009 in Math for Rufuson Oyinki

Question #136009
d). Solve for x in the following polynomials
(i). f(x) = 3x4 + 2x3 – 15x2 + 12x – 6
(ii). 2x4 + 3x3 – 13x2 – 6x + 8 = 0
1
Expert's answer
2020-10-13T19:52:27-0400

(i) 3x4+2x3-15x2+12x-6=0

Let f(x)=3x4+2x3-15x2+12x-6

d/dx(3x4+2x3-15x2+12x-6)=12x3+6x2-30x+12

∴f′(x)=12x3+6x2-30x+12

Here f(1) = - 4 < 0 and f (2) = 22 > 0

∴ Root lies between 1 and 2

x0=1+22=1.5

x0=1.5


1st iteration :


f(x0)=f(1.5)=3⋅1.54+2⋅1.53-15⋅1.52+12⋅1.5-6=0.1875

f′(x0)=f′(1.5)=12⋅1.53+6⋅1.52-30⋅1.5+12=21

x1=x0-f(x0)f′(x0)

x1=1.5-0.187521

x1=1.4911


2nd iteration :


f(x1)=f(1.4911)=3⋅1.49114+2⋅1.49113-15⋅1.49112+12⋅1.4911-6=0.0027

f′(x1)=f′(1.4911)=12⋅1.49113+6⋅1.49112-30⋅1.4911+12=20.3887

x2=x1-f(x1)f′(x1)

x2=1.4911-0.002720.3887

x2=1.4909


Approximate root of the equation 3x4+2x3-15x2+12x-6=0 using Newton Raphson method is 1.4909.

Now again using Newton Raphson Method to find the second root, now assuming initial condition to be -3 because while putting -3, the equation becomes nearer to zero. So the roots may be nearer to -3.


f(x)=3x4+2x3-15x2+12x-6

x0 = - 3


1st iteration :

 

f(x0)= f(-3) = 3⋅(-3)4+2⋅(-3)3-15⋅(-3)2+(12-3)-6=12

f′(x0)= f′(-3) =

12⋅(-3)3+6⋅(-3)2-(30-3)+12=-168

x1 = x0 - f(x0)f′(x0)

x1 = -3-12-168

x1 = -2.9286

 

2nd iteration :

 

f(x1) = f(-2.9286) = 3⋅(-2.9286)4+2⋅(-2.9286)3-15⋅(-2.9286)2+(12-2.9286)-6=0.6459

f′(x1) = f′(-2.9286) = 12⋅(-2.9286)3+6⋅(-2.9286)2-(30-2.9286)+12=-150.0875

x2 = x1 - f(x1)f′(x1)

x2 = -2.9286-0.6459-150.0875

x2 = -2.9243

 

3rd iteration :

 

f(x2) =  f(-2.9243) = 3⋅(-2.9243)4+2⋅(-2.9243)3-15⋅(-2.9243)2+(12-2.9243)-6=0.0023

f′(x2) = f′(-2.9243) = 12⋅(-2.9243)3+6⋅(-2.9243)2-(30-2.9243)+12=-149.041

x3 = x2 - f(x2)f′(x2)

x3 = -2.9243-0.0023-149.041

x3 = -2.9243


4th iteration :

 

f(x3) = f(-2.9243)=3⋅(-2.9243)4+2⋅(-2.9243)3-15⋅(-2.9243)2+(12-2.9243)-6=0

f′(x3) = f′(-2.9243)=12⋅(-2.9243)3+6⋅(-2.9243)2-(30-2.9243)+12=-149.0373

x4 = x3 - f(x3)f′(x3)

x4 = -2.9243-0-149.0373

x4 = -2.9243

Approximate root of the equation 3x4+2x3-15x2+12x-6=0 using Newton Raphson method is -2.9243

So, The two roots of our polynomial equation are found to be - 2.9243 and 1.4909.

The remaining two roots are not complex so it can’t be calculated.

-----------------------------------------------------------------------------------------------------------------------------------------------------------


(ii). 2x4 + 3x3 – 13x2 – 6x + 8 = 0

By Hit and Trial method, Putting x = -1 in the above equation:

 

2(-1)4 + 3(-1)3 – 13(-1)2 – 6(-1) + 8 = 0

0 = 0

 

Therefore, x = -1 is a solution of the above polynomial equation.

 

By hit and trial method, again putting x = 2 in the above equation:

 

2(2)4 + 3(2)3 – 13(2)2 – 6(2) + 8 = 0

0 = 0

 

Therefore, x = 2 is also a solution of the above polynomial equation.

 

Now the two roots of this equations are found to be -1, 2.

 

On dividing (2x4 + 3x3 – 13x2 – 6x + 8) by (x+1).(x-2), we get:

 

( 2x4 + 3x3 – 13x2 – 6x + 8)/((x+1)(x-2)) = 2x2 + 5x – 4

 

Now the equation can be written in the form,

 

2x4 + 3x3 – 13x2 – 6x + 8 = 0

(x + 1) (x - 2) (2x2 + 5x - 4) = 0

 

Using Quadratic formula on 2x2 + 5x – 4, we get:


x = "-5\/4\u00b1\u221a(\u3016(5\u3017^2+4*2*4)\/4"

x = "-5\/4+\u221a(57\/4)" and x = "-5\/4-\u221a(57\/4)"


So, the all roots of the equation are found to be

Solution: -1, 2, -5/4+√(57/4)  and -5/4-√(57/4)  






Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog